2014
DOI: 10.1016/j.amepre.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Distance to Store, Food Prices, and Obesity in Urban Food Deserts

Abstract: Background Lack of access to healthy foods may explain why residents of low-income neighborhoods and African Americans in the U.S. have high rates of obesity. The findings on where people shop and how that may influence health are mixed. However, multiple policy initiatives are underway to increase access in communities that currently lack healthy options. Few studies have simultaneously measured obesity, distance, and prices of the store used for primary food shopping. Purpose To examine the relationship am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
174
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(182 citation statements)
references
References 44 publications
(32 reference statements)
6
174
0
2
Order By: Relevance
“…27 However, price point has been shown to be more important than distance in healthy food choices among residents of low-income neighborhoods. 28 Expanding food options to smaller stores and direct-to-consumer marketing interventions, like food stands, community-supported agriculture and farmers' markets have shown a correlation with an increased consumption of fruits and vegetables. 5,[29][30][31][32] A study of women in North Carolina found that women who shopped at farmers' markets were more likely to consume more fruits and vegetables 30 and the use of an incentive program in New York was shown to increase shopping at markets and self-reported fruit and vegetable consumption.…”
Section: Incentivizing Fruit and Vegetables Purchases -Ferdinand Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…27 However, price point has been shown to be more important than distance in healthy food choices among residents of low-income neighborhoods. 28 Expanding food options to smaller stores and direct-to-consumer marketing interventions, like food stands, community-supported agriculture and farmers' markets have shown a correlation with an increased consumption of fruits and vegetables. 5,[29][30][31][32] A study of women in North Carolina found that women who shopped at farmers' markets were more likely to consume more fruits and vegetables 30 and the use of an incentive program in New York was shown to increase shopping at markets and self-reported fruit and vegetable consumption.…”
Section: Incentivizing Fruit and Vegetables Purchases -Ferdinand Et Almentioning
confidence: 99%
“…During 2017, Sankofa has transitioned the VDP to a SNAP-match program and increased the supplemental incentive amount in order to increase SNAP benefit usage at the markets. 28 Program participants presently receive a match of up to $20 of their SNAP purchases to acquire fruits and vegetables at the Sankofa Fresh Stop and Mobile Markets. Community and organizational partnerships also support Sankofa's efforts to host healthy cooking and gardening educational programs.…”
Section: Sankofa Fresh Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building supermarkets in food deserts to improve access to healthy foods may not be as effective as offering healthy products at more affordable prices 41 . This is because cost is considered the greatest barrier to a healthy diet, not physical distance or lack of information 42 .…”
Section: Cad Saúde Pública 2017; 33(2):e00145015mentioning
confidence: 99%
“…[6][7][8] Of studies finding improvements in healthy purchasing, these changes are not attributable to the use of the new retailer. 9,10 Evaluations also highlight the importance of in-store environment, including pricing, placement, and promotions, in motivating behavior change, 6,11 although none have explored shoppers' in-store experiences.…”
Section: Introductionmentioning
confidence: 99%